FEEDBACK: a SOFIA Legacy Program to Study Stellar Feedback in Regions of Massive Star Formation. (16th September 2020) - Schneider, N.; Simon, R.; Guevara, C.; Buchbender, C.; Higgins, R. D.; Okada, Y.; Stutzki, J.; Güsten, R.; Anderson, L. D.; Bally, J.; Beuther, H.; Bonne, L.; et al.
Abstract: FEEDBACK is a SOFIA (Stratospheric Observatory for Infrared Astronomy) legacy program dedicated to study the interaction of massive stars with their environment. It performs a survey of 11 galactic high mass star-forming regions in the 158 μ m (1.9 THz) line of [C ii ] and the 63 μ m (4.7 THz) line of [O i ]. We employ the 14 pixel Low Frequency Array and 7 pixel High Frequency Array upGREAT heterodyne instrument to spectrally resolve (0.24 MHz) these far-infrared fine structure lines. With a total observing time of 96h, we will cover ∼6700 arcmin 2 at 14.″1) angular resolution for the [C ii ] line and 6.″3 for the [O i ] line. The observations started in spring 2019 (Cycle 7). Our aim is to understand the dynamics in regions dominated by different feedback processes from massive stars such as stellar winds, thermal expansion, and radiation pressure, and to quantify the mechanical energy injection and radiative heating efficiency. This is an important science topic because feedback of massive stars on their environment regulates the physical conditions and sets the emission characteristics in the interstellar medium (ISM), influences the star formation activity through molecular cloud dissolution and compression processes, and drives the evolution of the ISM in galaxies. The [C ii ] line provides the kinematics of the gas and is one of the dominant cooling lines of gas for low to moderate densities and UV fields. The [O i ] line traces warm and high-density gas, excited in photodissociations regions with a strong UV field or by shocks. The source sample spans a broad range in stellar characteristics from single OB stars, to small groups of O stars, to rich young stellar clusters, to ministarburst complexes. It contains well-known targets such as Aquila, the Cygnus X region, M16, M17, NGC7538, NGC6334, Vela, and W43 as well as a selection of H ii region bubbles, namely RCW49, RCW79, and RCW120. These [C ii ] maps, together with the less explored [O i ] 63 μ m line, provide an outstanding database for the community. They will be made publically available and will trigger further studies and follow-up observations.